Optical Fiber Communication Conference (OFC) 2020 2020
DOI: 10.1364/ofc.2020.th1a.6
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Networks for Designing Integrated Photonics

Abstract: We present two different approaches to apply deep learning to inverse design for nanophotonic devices. First, we use a regression model, with device parameters as inputs and device responses as outputs, or vice versa. Second, we use a novel generative model to create a series of improved designs. We demonstrate them to design nanophotonic power splitters with multiple splitting ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Inspired by the previous work, [171] Tang et al reported a series of remarkable achievements in applying CVAE to design digital beam splitters. [172][173][174][175][176] Among them, the most detailed illustration is given in the literature. [172] This paper refined their method several times, resulting in the design of SOI-based power splitters with an ultra-compact footprint of 2.25 μm × 2.25 μm and ≈90% transmission efficiency over 1250-1800 nm wavelengths.…”
Section: Variational Autoencoder (Vae)mentioning
confidence: 99%
See 3 more Smart Citations
“…Inspired by the previous work, [171] Tang et al reported a series of remarkable achievements in applying CVAE to design digital beam splitters. [172][173][174][175][176] Among them, the most detailed illustration is given in the literature. [172] This paper refined their method several times, resulting in the design of SOI-based power splitters with an ultra-compact footprint of 2.25 μm × 2.25 μm and ≈90% transmission efficiency over 1250-1800 nm wavelengths.…”
Section: Variational Autoencoder (Vae)mentioning
confidence: 99%
“…Another example of VAE combined with the ADJ algorithm for the inverse design of a nanophotonic power splitter was reported in Ref. [178] Besides power splitters, [173][174][175][176]178] VAE has more recently achieved notable success in other silicon photonic devices, like digital multimode interference waveguides [179] and the Starshot lightsail, [180] see Figure 26a-d.…”
Section: Variational Autoencoder (Vae)mentioning
confidence: 99%
See 2 more Smart Citations
“…Models and simulations based on ML approaches can, for instance, quickly narrow down the parameter space of specific variables involved in fabrication processes [18,181,182]. They can also be used to control, tweak or even design ad hoc properties of materials [131], heterostructures [9,132] and devices [19, 136,137], again while being suitable for fabrication strategies that require large-scale, fast and automated production.…”
Section: Color Center Synthesis and Stabilitymentioning
confidence: 99%